2014
DOI: 10.1097/01.ogx.0000451484.02983.78
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival With Bevacizumab in Advanced Cervical Cancer

Abstract: Background-Vascular endothelial growth factor (VEGF) promotes angiogenesis, a mediator of disease progression in cervical cancer. Bevacizumab, a humanized anti-VEGF monoclonal antibody, has single-agent activity in previously treated, recurrent disease. Most patients in whom recurrent cervical cancer develops have previously received cisplatin with radiation therapy, which reduces the effectiveness of cisplatin at the time of recurrence. We evaluated the effectiveness of bevacizumab and nonplatinum combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
183
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(196 citation statements)
references
References 19 publications
5
183
0
8
Order By: Relevance
“…Finally, all data from trials using bevacizumab, including GOG 240 [2], RTOG 0417 [4], and the study of Zighelboim et al [5] are consistent with significant toxicities, particularly grade 3-4 bleeding, thromboembolic events, and GI fistulas as well as unanticipated hospital admissions for supportive care. This raises concerns about the anticipated goals of care, also given the absence of change in quality of life [2] particularly in heavily pretreated patients with residual toxicities.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Finally, all data from trials using bevacizumab, including GOG 240 [2], RTOG 0417 [4], and the study of Zighelboim et al [5] are consistent with significant toxicities, particularly grade 3-4 bleeding, thromboembolic events, and GI fistulas as well as unanticipated hospital admissions for supportive care. This raises concerns about the anticipated goals of care, also given the absence of change in quality of life [2] particularly in heavily pretreated patients with residual toxicities.…”
mentioning
confidence: 68%
“…GOG 240 was the first study involving an agent targeting angiogenesis, bevacizumab, which demonstrated a significant prolongation of survival in advanced, recurrent or persistent cervical cancer [2]. Tewari et al [2] reported a 3.7-month improvement in median overall survival (OS) of patients with recurrent, persistent, or metastatic cervical cancer when treated with systemic chemotherapy and bevacizumab, compared to chemotherapy alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, following the ASCO 2013 presentation of GOG 240, the cisplatin-paclitaxel-bevacizumab triplet was listed as category 2A nearly eight months in advance of the paper. With the primary manuscript now published [10] it may flip to category 1 but without US Food & Drug Administration approval, only some patients with HMOs or PPOs will be able to receive the drug, while those on Medicare and Medicaid will not. Although London's Guardian reported that following publication of the primary GOG 240 manuscript, England's Cancer Drug Fund made bevacizumab available for advanced cervical cancer [11], we do not have such a mechanism in the United States that specifically is charged with making available drugs that are efficacious but not cost-effective.…”
Section: Editorialmentioning
confidence: 99%
“…[22][23][24][25] This oncologic milestone represents the first time a targeted agent has resulted in an overall survival advantage in the gynecologic cancer arena. Ultimately, on August 14, 2014, the US Food and Drug Administration (FDA), following priority review, expanded the indication of bevacizumab to include advanced cervical cancer based on the findings of GOG 240.…”
Section: Introductionmentioning
confidence: 99%